Surat-surat Tengku Pangeran Siak: Sebuah Reportase Perjalanan untuk Raffles - Hazmirullah Hazmirullah; Titin Nurhayati Ma’mun; Undang A. Darsa (Manuskripta, 2016)
Tengku Pangeran Siak was one of the important figures in the plan of the British occupation of the Java. He was a messenger, even considered as the best assistant, of Thomas Stamford Raffles. In addition to its role in delivering some letters of diplomacy, he also was assigned to persuade some Malay authorities into agreeing British plan to occupy the land of Java. He sailed from Malacca to Java in the last week of December 1810 and then returned in early May 1811. During his trip to Java, he sent five letters to Raffles. This article presents a discussion of the letters of Tengku Pangeran Siak using journalism perspective. The text in the letters were considered to conform to the principles of journalism, such as factual, comprehensive and proportional. The factuality of that reportages was obtained after they were discussed with other various manuscripts and historical archives. Thus, the information in the text of Tengku Pangeran Siak letters had a high level of accuracy. === Tengku Pangeran Siak adalah salah satu sosok penting dalam rencana pendudukan Inggris terhadap pulau Jawa. Ia merupakan salah seorang utusan, bahkan didapuk sebagai best assistant, Thomas Stamford Raffles. Selain berperan mengantarkan surat diplomasi, ia juga ditugaskan untuk “merayu” para penguasa sejumlah negeri di tanah Melayu agar menyetujui langkah Inggris untuk menduduki Jawa. Ia berlayar dari Malaka menuju Jawa pada pekan terakhir Desember 1810 dan baru kembali awal Mei 1811. Sepanjang pelayaran ke Jawa, ia mengirimkan lima pucuk surat kepada Raffles. Artikel ini menyajikan pembahasan teks surat-surat Tengku Pangeran Siak dalam perspektif jurnalisme. Teks di dalam surat-surat itu telah memenuhi prinsip-prinsip yang dianut oleh jurnalisme, di antaranya faktual, komprehensif, dan proporsional. Kefaktualan “reportase” itu diperoleh setelah teks surat-surat tersebut “didialogkan” dengan berbagai naskah lain dan arsip sejarah. Dengan demikian, informasi di dalam teks surat-surat Tengku Pangeran Siak memiliki tingkat akurasi yang tinggi.